Naphthoquinones as a Promising Class of Compounds for Facing the Challenge of Parkinson's Disease - Thaís Barreto Santos; Leonardo Gomes Cavalieri de Moraes; Paulo Anastácio Furtado Pacheco; Douglas Galdino dos Santos; Rafaella Machado de Assis Cabral Ribeiro; Caroline dos Santos Moreira; David Rodrigues da Rocha (MDPI AG, 2023)
Parkinson's disease (PD) is a degenerative disease that affects approximately 6.1 million people and is primarily caused by the loss of dopaminergic neurons. Naphthoquinones have several biological activities explored in the literature, including neuroprotective effects. Therefore, this review shows an overview of naphthoquinones with neuroprotective effects, such as shikonin, plumbagin and vitamin K, that prevented oxidative stress, in addition to multiple mechanisms. Synthetic naphthoquinones with inhibitory activity on the P2X7 receptor were also found, leading to a neuroprotective effect on Neuro-2a cells. It was found that naphthazarin can act as inhibitors of the MAO-B enzyme. Vitamin K and synthetic naphthoquinones hybrids with tryptophan or dopamine showed inhibition of the aggregation of α-synuclein. Synthetic derivatives of juglone and naphthazarin were able to protect Neuro-2a cells against neurodegenerative effects of neurotoxins. In addition, routes for producing synthetic derivatives were also discussed. With the data presented, 1,4-naphthoquinones can be considered as a promising class in the treatment of PD and this review aims to assist the scientific community in the application of these compounds. The derivatives presented can also support further research that explores their structures as synthetic platforms, in addition to helping to understand the interaction of naphthoquinones with biological targets related to PD.